2018
DOI: 10.1371/journal.pone.0193387
|View full text |Cite
|
Sign up to set email alerts
|

The BPA-substitute bisphenol S alters the transcription of genes related to endocrine, stress response and biotransformation pathways in the aquatic midge Chironomus riparius (Diptera, Chironomidae)

Abstract: Bisphenol S (BPS) is an industrial alternative to the endocrine disruptor bisphenol A (BPA), and can be found in many products labeled “BPA-free”. Its use has grown in recent years, and presently it is considered a ubiquitous emerging pollutant. To date there is a lack of information on the effects of BPS on invertebrates, although they represent more than 95% of known species in the animal kingdom and are crucial for the structure and proper function of ecosystems. In this study, real-time RT-PCR was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 62 publications
1
22
0
1
Order By: Relevance
“…There are many studies that have shed some light on the possible unwanted effects of BPA; however, there are very few investigations on the effects of BPA alternatives, such as BPF and/or BPS (Herrero et al, ). In the present study, we assessed the cytotoxic and genotoxic effects of BPA and its alternatives (BPF and BPS) on RWPE‐1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies that have shed some light on the possible unwanted effects of BPA; however, there are very few investigations on the effects of BPA alternatives, such as BPF and/or BPS (Herrero et al, ). In the present study, we assessed the cytotoxic and genotoxic effects of BPA and its alternatives (BPF and BPS) on RWPE‐1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphenol F (BPF) differs from BPA by the absence of two methyl groups bound to the central carbon atom of its molecule that results in its lower polarity. On the other hand, because of the presence of two phenolic groups on each side of the sulphonic group, BPS has a similar chemical structure to BPA, but higher thermal stability [9,10]. Bisphenol A (BPA) is formed by condensation of an acetone molecule and two molecules of phenol, catalysed by hydrogen chloride or an ion-exchange resin [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many pollutants previously considered only in light of their endocrine disruption capability have recently also been implicated in the activation of several immune pathways involved in both autoimmune disease development and autoimmune reactivity provocation, as estrogen has also been reported as playing an important role in the immune system altering inflammatory mediator responses and humoral immune response (Lee et al 1994;Yoshino et al 2003;Haghmorad et al 2014). These include contaminants such as metals; PFAS; plastic components, such as BPA; and plasticizers, like phthalates (Dong et al 1998;Kharrazian 2014;Hansen et al 2015), although studies are still incipient in this regard. Although many in vitro studies have demonstrated cytokine effects, among other immune responses by several pollutants (Shertzer et al 1985;Li et al 2013), only assessments performed through the drinking water exposure route in mammals (mice, rats, rabbits) in laboratory conditions or concerning human cohorts are included herein.…”
Section: Immune Suppression Effects Of Drinking Water Contaminants Anmentioning
confidence: 99%